2020
DOI: 10.1038/s41598-020-62265-8
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective qualitative report of symptoms and safety from transcranial focused ultrasound for neuromodulation in humans

Abstract: Low intensity transcranial focused ultrasound (LifU) is a promising method of non-invasive neuromodulation that uses mechanical energy to affect neuronal excitability. LIFU confers high spatial resolution and adjustable focal lengths for precise neuromodulation of discrete regions in the human brain. Before the full potential of low intensity ultrasound for research and clinical application can be investigated, data on the safety of this technique is indicated. Here, we provide an evaluation of the safety of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 52 publications
1
61
1
Order By: Relevance
“…(Mueller et al, 2016). Though no human studies have reported any permanent adverse effects from application of low-intensity TUS (Legon et al, 2020), a single sheep study showed small microhemorrhages at the cortical site of sonication, albeit after prolonged repetitive (>500) trials at intensities (I SPPA = 10.5 W/cm 2 ) higher than used in our study (Gaur et al, 2020;Lee et al, 2016c). The absence of edema, necrosis, or local inflammatory responses, as well as a lack of control group may implicate post-mortem brain extraction as the cause of these findings, rather than sonication itself.…”
Section: Safetymentioning
confidence: 99%
“…(Mueller et al, 2016). Though no human studies have reported any permanent adverse effects from application of low-intensity TUS (Legon et al, 2020), a single sheep study showed small microhemorrhages at the cortical site of sonication, albeit after prolonged repetitive (>500) trials at intensities (I SPPA = 10.5 W/cm 2 ) higher than used in our study (Gaur et al, 2020;Lee et al, 2016c). The absence of edema, necrosis, or local inflammatory responses, as well as a lack of control group may implicate post-mortem brain extraction as the cause of these findings, rather than sonication itself.…”
Section: Safetymentioning
confidence: 99%
“…Following these, a third recent report assembled data from 64 subjects over 7 experiments. [53] Events were classified as possibly/probably related and unlikely/unrelated to ultrasound stimulation. For the first class, neck pain, difficulty paying attention, muscles twitches and anxiety were described (7/64).…”
Section: Safety Of Transcranial Ultrasound Therapiesmentioning
confidence: 99%
“…[Correction added after publication on 02 December 2020: In the last paragraph of Section 5, the missing reference, [53], was added. ]…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Although our study administered less ultrasound intensities than those 450 applied in (Legon et al, 2020) and even much less than the FDA's guideline 451 (ISPPA ≤ 190 W/cm 2 ) (FDA, 2008), we were also cautious about the tFUS 452 safety on the subjects during the experiment sessions. We surveyed the 453 subjects with a brief questionnaire for report of symptoms, such as headache, 454 neck pain, dental pain, nausea, dizziness, anxiety, abnormal muscle 455 contractions etc., before and after tFUS sessions.…”
mentioning
confidence: 98%
“…Low intensity tFUS neuromodulation is deemed as generally safe without 447 inducing serious adverse effects on humans upon careful control of the 448 ultrasound intensities (ISPPA: 11.56-17.12 W/cm 2 ) (Legon et al, 2020).…”
mentioning
confidence: 99%